2023
DOI: 10.3390/app13179705
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Microplastics in Aquaculture Systems (Fish, Mussel, and Water Samples) by FTIR, Scanning Electron Microscopy–Energy Dispersive Spectroscopy and Micro-Raman Spectroscopies

Kleopatra Miserli,
Christos Lykos,
Angelos G. Kalampounias
et al.

Abstract: In the last decade, plastic waste has become one of the main threats to marine ecosystems and their biodiversity due to its abundance and increased persistence. Microplastics can be classified as either primary, i.e., fabricated for commercial use, or secondary, i.e., resulting from the fragmentation/weathering processes of larger plastic pieces in the environment. In general, microplastics are detected in a number of aquatic organisms (e.g., fish, bivalves, mollusks, etc.) with alarming effects on their healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…The results from a study conducted by Vasanthni et al have confirmed that fibers were the predominant type of MPs observed in the mussel P. viridis from Kasimedu, Chennai, India, followed by spheres, flakes, sheets, and fragments [67]. Furthermore, in a study conducted by Gündo gdu et al, the MPs found in mussels bought at the Turkish market in five different cities were identified as fibers (62.7%) and fragments (37.3%) [94]. Fragments or fibers were also mainly recorded as the dominant shape of MPs found in the edible green-lipped mussel P. viridis by using an automated mapping technique of Raman microspectroscopy [97].…”
Section: Different Shapes Of Microplastics Found In Mussel Digestive ...mentioning
confidence: 83%
See 3 more Smart Citations
“…The results from a study conducted by Vasanthni et al have confirmed that fibers were the predominant type of MPs observed in the mussel P. viridis from Kasimedu, Chennai, India, followed by spheres, flakes, sheets, and fragments [67]. Furthermore, in a study conducted by Gündo gdu et al, the MPs found in mussels bought at the Turkish market in five different cities were identified as fibers (62.7%) and fragments (37.3%) [94]. Fragments or fibers were also mainly recorded as the dominant shape of MPs found in the edible green-lipped mussel P. viridis by using an automated mapping technique of Raman microspectroscopy [97].…”
Section: Different Shapes Of Microplastics Found In Mussel Digestive ...mentioning
confidence: 83%
“…These elements are characteristic of different types of plastics, can be detected using methods such as SEM-EDS, were identified as MPs (Figure 4a), and were included in further data analysis. On the contrary, a particle that consisted of a larger portion of oxygen and silicon atoms was identified as a mineral particle (Figure 4b) and was not taken into account, as was found in many studies [32,51,[93][94][95]. Analyzing cryosections of a mussel's digestive gland with SEM-EDS could offer a good way to perform detection.…”
Section: Identification Of Microplastics Found In Mussel Digestive Gl...mentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple analytical techniques based on mass or particle size determinations are usually required to obtain information about the concentration, chemical composition, and shape of MPs and NPs. MP identification techniques include microscopic observations [36], µ-Raman [37,38], Fourier transform infrared spectroscopy (FTIR) [38,39], µ-FTIR [31], scanning electron microscopy (SEM)/energy dispersive X-ray spectroscopy (EDX) [36,38], and micro-optofluidic platform [36,40], while the NPs have been evaluated using thermal desorption-proton transfer reaction-mass spectrometry (TD-PTR-MS) [29,41], dynamic light scattering (DLS) [26,42,43], transmission electron microscopy (TEM) [44,45], surface-enhanced Raman spectroscopy (SERS) [46], and pyrolysis-gas chromatography/mass spectrometry Py-GC/MS analytical techniques [47]. Since no single analytical method is able to obtain the physical (size, shape, and color) and chemical (polymer type) characteristics of MPs in a single step, the combination of several parallel approaches should be applied and considered.…”
Section: Introductionmentioning
confidence: 99%